The chemical biology of hydrogen sulfide and related hydropersulfides: interactions with biologically relevant metals and metalloproteins. (April 2020) - Fukuto, Jon M.; Vega, Valeria Suarez; Works, Carmen; Lin, Joseph
Abstract: Hydrogen sulfide and related/derived persulfides (RSn H, RSSn R, n > 1) have been the subject of recent research interest because of their reported physiological signaling roles. In spite of their described actions, the chemical/biochemical mechanisms of activity have not been established. From a chemical perspective, it is likely that metals and metalloproteins are possible biological targets for the actions of these species. Thus, the chemical biology of hydrogen sulfide and persulfides with metals and metalloproteins will be discussed as a prelude to future speculation regarding their physiological function and utility.